ANALISIS PENGARUH STRUKTUR MODAL, NILAI PERUSAHAAN, KINERJA KEUANGAN, DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2020-2024 - Hutagalung, Sindy Aura Puspita Br; Parhusip, Austin Alexander (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
This study aims to analyze the effect of capital structure, firm value, financial performance, and dividend policy on stock prices in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employs a quantitative approach with an associative research type. The data used are secondary data obtained from financial statements through the official IDX website (https://www.idx.co.id). The population consists of 51 companies, of which 10 were selected as samples using purposive sampling, resulting in 50 observations. Data were analyzed using multiple linear regression analysis with a 5% significance level. The results show that, partially, capital structure, firm value, and financial performance have a significant effect on stock prices, while dividend policy has no positive and significant effect. Simultaneously, capital structure, firm value, financial performance, and dividend policy have a significant effect on stock prices. These findings indicate that investors tend to consider financial stability and company growth prospects rather than dividend distribution policies in making investment decisions.